Penerapan Model Discovery Learning untuk Meningkatkan Hasil Belajar Bilangan Berpangkat pada Siswa Kelas X Madrasah Aliyah Swasta Paringgonan - Irmadani Parapat (PANTAK: Jurnal Penelitian Tindakan Kelas, 2025)
This study aims to improve student learning outcomes on the topic of exponents through the application of the Discovery Learning model in class X of Paringgonan Private Islamic Senior High School in the 2024–2025 Academic Year. This study is a Classroom Action Research (CAR) carried out in two cycles, each including the planning, implementation, observation, and reflection stages. The research subjects were 32 students. Data collection techniques used learning outcome tests and student activity observation sheets. The results showed an increase in the class average score from 62 in the pre-action to 73 in cycle I and 86 in cycle II. The percentage of learning completeness also increased from 34% to 63% and finally reached 90% in cycle II. This increase shows that the application of the Discovery Learning model is effective in helping students understand the concept of exponents more deeply and increasing student learning activity and motivation.